Can supplemented skim milk (skm) boost your gut health? - Carvalho, Nelson Mota de (2022)
The incorporation of functional ingredients, such as prebiotics and probiotics in food matrices, became a common practice in the human diet to improve the nutritional value of the food product itself. Worldwide, skim milk (SKM) is one of the most consumed food matrices, comprising all the essential nutrients desired for a balanced diet. Thus, the modulation of the human gut microbiota by SKM supplemented with different well-known functional ingredients was evaluated. Four well-studied prebiotics, fructo-oligosaccharides (FOS), galacto-oligosaccharides (GOS), mannanoligosaccharides (MOS) and inulin, and one probiotic product, UL-250® (Saccharomyces boulardii) were added at 1% (w/v) to SKM and subjected to a gastrointestinal in vitro model. The impact of each combination on gut microbiota profile and their fermentation metabolites (i.e., short-chain fatty acids–SCFA) was assessed by quantitative polymerase chain reaction (qPCR) and high-performance liquid chromatography (HPLC), respectively. The addition of FOS to SKM had promising results, showing prebiotic potential by promoting the growth of Lactobacillus, Bifidobacterium, and Clostridium cluster IV. Moreover, the increment of SCFA levels and the decrease of total ammonia nitrogen were observed throughout colonic fermentation. Overall, these results demonstrate that the combination SKM + FOS was the most beneficial to the host’s health by positively modulating the gut microbiota.